INFLUENCE OF GENETIC AND NON-GENETIC FACTORS ON QUANTITY AND QUALITY OF WOOL FROM SHEEP REARED AT RAWALAKOT AZAD JAMMU AND KASHMIR - Qureshi; M. A.; S. A. Khan; M. Shafique; N. Sabir; G. Ahmed (Journal of Animal and Plant Sciences, 2013)
The data on body weight and greasy wool yield was collected from 35 animals during July, 2007 to July, 2009. The animals were weighed in the first week of each month and shorn annually in March. The least squares means for annual greasy fleece yield, staple length, fiber diameter, medullation, clean yield percent, clean wool yield and wool bulk were 2.28±0.20 kg, 7.66±0.44cm, 26.23±0.60 percent, 69.67±2.34 percent, 1.59±0.14 kg cm3/gm, respectively. The analysis of variance revealed that the years of shearing and breed were the significant (P<0.05) sources of variation for greasy fleece yield, however, sex showed non significant difference. The least squares means for greasy fleece yield was 2.29±0.10 kg 2.84±0.91 and 2.34±0.09,kg during 2007, 2008 and 2009, respectively. However, least squares means for Crossbred, Poonchi and Rambuillet genotype was 2.19±0.08, 1.92±0.12 and 2.36±0.091kg, respectively. The differences due to year of shearing was significant (P<0.05), however, sex and breed were non significant for staple length. Least squares means for staple length was 8.75±0.58, 7.75±0.53 and 9.46±0.53 cm during the study period (2007-09). However, it was 8.88±0.05, 7.89±0.67 and 9.00±0.48 cm, for Crossbred, Poonchi and Rambuillet genotypes, respectively. Males produced more staple length (9.01±0.78 cm) when compared with female lambs (8.09±0.29 cm). Least squares means for fiber diameter and medullation were 27.47±0.09, 26.77±0.65, 27.06±0.65 micron and 6.40±1.28, 5.77±1.17, 5.89±1.17 percent during 2007 to 2009, and for Crossbred, Poonchi and Rambuillet sheep were 26.36±0.83, 27.93±0.58 and 20.02±0.65 cm and 3.08±1.49, 8.89±1.05 and 6.09±1.17 percent respectively. Analysis of variance for clean yield percent and wool bulk gave non significant difference for all factors studied. Clean yield percent was almost similar during the rearing period but it was higher (71. 08±2.12 %) in Poonchi and female (70.47±1.08%) sheep. Least squares means for wool bulk were similar but it was high in Poonchi (26.46±0.49 cm3 /gm) and female animals (26.18±0.25 cm3 /gm). There was an overall improvement in greasy wool yield in crossbred lambs compared to local Poonchi sheep. Crossing of local sheep with exotic Rambouillet results in the overall improvement in wool quality. However, it was recommended that the estimated environmental effects are important and needs more extensive study for improvement and planning in sheep breeding in future
Keywords: Sheep; Rawalakot; Non-Genetic Factors; Fleece yield; Staple length